Gelation of covalently edge-modified laponites in aqueous media. 1. rheology and nuclear magnetic resonance - Patil, Suhas P.; Mathew, Renny; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Mahesh, T. S.; Kumaraswamy, Guruswamy (Journal of Physical Chemistry B, 2008)
We describe the covalent modification of the edges of laponite with organic groups and the influence of this modification on gelation behavior. We compare three materials: an unmodified laponite, a laponite edge modified with a trimethyl moiety (MLap), and an octyldimethyl moiety (OLap). Gelation is investigated using rheology and NMR T-1 relaxation measurements and nuclear Overhauser enhancement spectroscopy (NOESY). MLap and OLap show qualitatively different gelation. Gelation of MLap is very similar to laponite: MLap gels over the same time scale as laponite and has about the same solid modulus, and the MLap gel is almost as transparent as laponite. In contrast, OLap gels rapidly relative to laponite and forms a weak, turbid gel. We believe that gelation in laponite and MLap results from the formation of a network of well-dispersed platelets (or a few platelets), while in OLap, gelation results from a network of stacks of several platelets. NMR relaxation measurements indicate that gelation does not affect the average relaxation of water protons. However, T, increases marginally for the protons in the organic moieties in MLap and decreases for protons in the organic moieties in OLap. Relaxation measurements, analyses of line width, and NOESY taken together suggest that, in OLap, gelation is a consequence of association of the organic moieties on the laponite edges, and that this association strengthens with time. Thus, the time-dependent changes in NMR suggest a structural origin for the time-dependent changes in the rheological behavior.